Proteomic analysis of hemolymph during immune response of Drosophila melanogaster larvae by UPLC-MS. - Jetzinger, Barbara (Jihočeská univerzita, 2018)
The aim of this study was the identification of proteins in larval hemolymph of Drosophila melanogaster which are allocated to immune response after parasitoid egg infection of Leptopilina boulardi. The proteins were determined by means of UPLC-MS.
Proteomic analysis of hemolymph during immune response of Drosophila melanogaster larvae by UPLC-MS.